Lifestyle behaviors and cardiovascular risk factors in transgender versus cisgender stroke survivors - Roham Sarmadian; Ajith Vemuri; Vida Abedi; Ramin Zand (PLoS ONE, 2025)
Transgender individuals represent a vulnerable population with unique healthcare needs. Despite facing health disparities, there is limited research on the characteristics and stroke risk factors among transgender stroke survivors. We extracted and analyzed data from the 2020–2022 Behavioral Risk Factor Surveillance System (BRFSS) to study stroke risk factors among transgender stroke survivors and to compare them to cisgender stroke survivors. cisgender stroke survivors were paired with transgender stroke survivors using a 1:2 propensity score matching (PSM) ratio. Demographic characteristics, lifestyle factors, and vascular risk factors were assessed using univariate and multivariate logistic regression models. Out of 29,628 individuals with a history of stroke, we identified 189 transgender stroke survivors and matched them with 378 cisgender stroke survivors. Transgender individuals exhibited a higher odds of reporting a history of stroke compared to cisgenders (adjusted odds ratio[aOR]=1.692, 95% CI 1.645–1.741). Hypertension (57.8%), depression (54.3%), hypercholesterolemia (52%), and obesity (44.7%) were the most common risk factors for transgender stroke survivors. Transgender stroke survivors had higher odds of lifestyle risk factors such as e-cigarette smoking (aOR=3.651, 95%CI 1.373–9.705), binge drinking (aOR=2.519, 95%CI 1.088–5.832), alcohol consumption (aOR=2.147, 95%CI 1.049–4.395), and tobacco smoking (aOR=2.030, 95%CI 1.214–3.395). In conclusion, transgender stroke survivors may face significant challenges due to elevated modifiable risk factors, especially lifestyle-related ones. Recognizing these specific risk factors is crucial for targeted interventions for transgender stroke survivors.